Speech Sound Disorders in Children: An Articulatory Phonology Perspective - Namasivayam, Aravind Kumar; Coleman, Deirdre; O’Dwyer, Aisling; van Lieshout, Pascal (Frontiers in Psychology, 2020)
Speech Sound Disorders (SSDs) is a generic term used to describe a range of difficulties producing speech sounds in children (McLeod & Baker, 2017). The foundations of clinical assessment, classification and intervention for children with SSD have been heavily influenced by psycholinguistic theory and procedures, which largely posit a firm boundary between phonological processes and phonetics/articulation (Shriberg, 2010). Thus, in many current SSD classification systems the complex relationships between the aetiology (distal), processing deficits (proximal) and the behavioural levels (speech symptoms) is under-specified (Terband et al., 2019). It is critical to understand the complex interactions between these levels as they have implications for differential diagnosis and treatment planning (Terband et al., 2019). There have been some theoretical attempts made towards understanding these interactions (e.g. Byun & Tessier, 2016) and characterizing speech patterns in children either solely as the product of speech motor performance limitations or purely as a consequence of phonological/grammatical competence has been challenged (Byun, 2012; Inkelas & Rose, 2007). In the present paper, we also intend to reconcile the phonetic-phonology dichotomy and discuss the interconnectedness between these levels and the nature of SSDs using an alternative perspective based on the notion of an articulatory “gesture” within the broader concepts of the Articulatory Phonology model (AP; Browman & Goldstein, 1992). The articulatory “gesture” serves as a unit of phonological contrast and characterization of the resulting articulatory movements (Browman & Goldstein, 1992; Van Lieshout & Goldstein, 2008). We present evidence supporting the notion of articulatory gestures at the level of speech production and as reflected in control processes in the brain and discuss how an articulatory “gesture”-based approach can account for articulatory behaviours in typical and disordered speech production (Pouplier & Van Lieshout, 2016; Van Lieshout, 2004). Specifically, we discuss how the AP model can provide an explanatory framework for understanding SSDs in children. Although other theories may be able to provide alternate explanations for some of the issues we will discuss, the AP framework in our view generates a unique scope that covers linguistic (phonology) and motor processes in a unified manner.